Tissue Inhibitor of Metalloproteinase-3 Promotes Schwann Cell Myelination - Jihyun Kim; Anthony Elias; Taeweon Lee; Patrice Maurel; Haesun A. Kim (ASN Neuro, 2017)
Tissue inhibitor of metalloproteinase-3 (TIMP-3) inhibits the activities of various metalloproteinases including matrix metalloproteinases and ADAM family proteins. In the peripheral nervous system, ADAM17, also known as TNF-α converting enzyme (TACE), cleaves the extracellular domain of Nrg1 type III, an axonal growth factor that is essential for Schwann cell myelination. The processing by ADAM17 attenuates Nrg1 signaling and inhibits Schwann cell myelination. TIMP-3 targets ADAM17, suggesting a possibility that TIMP-3 may elicit a promyelinating function in Schwann cells by relieving ADAM17-induced myelination block. To investigate this, we used a myelinating coculture system to determine the effect of TIMP-3 on Schwann cell myelination. Treatment with TIMP-3 enhanced myelin formation in cocultures, evident by an increase in the number of myelin segments and upregulated expression of Krox20 and myelin protein. The effect of TIMP-3 was accompanied by the inhibition of ADAM17 activity and an increase in Nrg1 type III signaling in cocultures. Accordingly, the N-terminus fragment of TIMP-3, which exhibits a selective inhibitory function toward ADAM17, elicited a similar myelination-promoting effect and increased Nrg1 type III activity. TIMP-3 also enhanced laminin production in cocultures, which is likely to aid Schwann cell myelination.